Self-efficacy as a mediator in the relationship between clinical learning environment and core nursing competence of intern nursing students: a multicentre cross-sectional study - Xiaoxia Zhang; Xianqiong Feng; Lan Fu; Yunxia Pu; Hongmei Xie; Ting Long; Xiaotian Su; Xiaojuan Feng (BMJ Open)
Objective The aim of this study was to examine the relationships between Chinese intern nursing students’ self-efficacy, the clinical learning environment, and core nursing competence. In addition, self-efficacy was investigated as a mediator in the association between the clinical learning environment and core nursing competence.Design This study used a cross-sectional, descriptive research design.Setting 15 nursing colleges and universities in China were the setting for the study.Participants The participants were 552 nursing student interns.Primary and secondary outcome measures The participants completed measures of general self-efficacy and nursing student core competencies.Results Participants’ mean scores indicated they were satisfied with the clinical learning environment (123.02±19.62), their self-efficacy was at a medium-high level (29.71±5.25), and their core competence was at the upper intermediate level (148.73±22.63). Core nursing competence was positively correlated with self-efficacy and the clinical learning environment (r=0.597, p<0.001; r=0.549, p<0.001). The clinical learning environment (β=0.362, p<0.001), duration of clinical practice (β=0.131, p<0.001) and self-efficacy (β=0.406, p<0.001) were identified as significant predictors of core nursing competence. Self-efficacy partially mediated the association between perception of the clinical learning environment and core competence level, accounting for 45.88% of the overall effect.Conclusions Self-efficacy played a role in explaining the beneficial association between the clinical learning environment and core nursing competence among Chinese intern nursing students. These findings suggest that nursing managers and educators should initially promote nursing students’ self-efficacy to increase their confidence in overcoming clinical obstacles, and subsequently cultivate their core nursing competence.